Palabras desnudas. Sobre la fuerza expresiva de la poesía española traducida al polaco por Carlos Marrodán Casas - Gutkowska, Katarzyna (Romanica Silesiana)
The article explores the characteristics of the poetic translation as well as the techniques used by Carlos Marrodán Casas (without a doubt one of the best known Polish translators of Spanish and Ibero-American Narrative) who has dedicated himself — more than once — to translating Spanish poetry. The study focuses on his attempts to introduce a selection of poems by Ángel González and Francisco Brines to the Polish readers. Both poets represent the Generation of 1950s and are perceived as two of the most creative authors of the lyrical, self-oriented poetry that goes beyond the limitations of the self by broadening the scope of expression with the wider and universalistic perspective. The accurateness of stylistic and formal choices made by the translator is examined on the basis of the translation criticism, in its descriptive as well as evaluative dimension. Key words: Carlos Marrodán Casas, Generation of 1950, translation criticism, contemporary Spanish poetry.